Factors Associated with Breakfast Habits of Elementary School Children at UPT SDN 101878 Kanan I Buntu Bedimbar Village, Tanjung Morawa District - Bleszynski S, Monica; Angkat, Abdul Hairuddin (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2023)
The research aims to determine the factors associated with the breakfast habits of school children. The study was conducted at UPT SDN 101878 Kanan I, Buntu Bedimbar, commencing in May 2023, using an observational analytical research method with a cross-sectional design. The research sample consisted of fourth and fifth-grade students, with a total sample size of 46 students. Data collection was carried out through questionnaires and interviews, and statistical analysis was performed using the Chi-Square test. The research results indicated that the availability of breakfast was correlated with breakfast habits in 65.2% of cases. The pocket money category was correlated with breakfast habits in 71.7% of cases among the 33 students, while the mother's occupation category was correlated with breakfast habits in 58.6% of cases among the 27 students. Cross-tabulation results demonstrate a significant correlation between these factors and breakfast habits. In conclusion, the presence of a morning breakfast's availability is related to breakfast habits, with a p-value of 0.006, rejecting the null hypothesis (Ho). There is also a relationship between pocket money and breakfast habits, with a p-value of 0.007, rejecting the null hypothesis (Ho), as well as a connection between the mother's occupation and breakfast habits, with a p-value of 0.038, rejecting the null hypothesis (Ho).